The craft of scientific writing - Alley, Michael (Springer, 1996)
Written for use as a text in courses on scientific writing, the book includes many useful suggestions about approaching a wide variety of writing tasks - from laboratory reports to grant proposals, from internal communications to press releases - as well as a concise guide to style and usage appropriate for scientific writing. The book will also be useful for self-study and it will be an important reference for all scientists and engineers who need to write about their work. Topics covered include deciding where to begin - structure: organizing your documents; providing depth, transitions, and emphasis - language: being precise, clear, and concise; being forthright, familiar, and fluid - illustration: making the right choices; creating the best designs - handling special situations - and actually sitting down to write: drafting, revising, finishing.